Hukum Utama Dalam Mempersiapkan Khotbah - Hasanema Wau (Jurnal Teologi dan Pelayanan Kerusso, 2021)
A sermon today (here) is built from a text written thousands of years ago and addressed to a specific person or community. Serious efforts are needed to bridge the cultural gap between today's readers and first readers. Two temptations to watch out for: first, focus on exploring and describing various historical arguments. The sermon focuses on patterns of interpretation of the biblical texts relating to the past in the area of ​​Israel and beyond. Second, the focus is to be relevant, so that it ignores what the author intends, what is understood by the recipient of the letter. The Scriptures are not a letter that is only able to be solved by an expert in a line of academic degrees. On the one hand it must find out the meaning of the text (for writers and readers), on the other hand it must find principles that can be applied now and here. Balance is a demand! The Word of God speaks to all generations, so it is not enough to rediscover the original meaning of a passage without describing the significance of the passage for today. Abstrak Indonesia Sebuah khotbah hari ini (di sini) dibangun dari teks yang ditulis ribuan tahun yang lalu dan ditujukan kepada orang atau komunitas tertentu. Upaya serius diperlukan untuk menjembatani kesenjangan budaya antara pembaca saat ini dan pembaca pertama. Dua godaan yang harus diwaspadai: pertama, fokus mengeksplorasi dan mendeskripsikan berbagai argumen sejarah. Khotbah berfokus pada pola penafsiran teks-teks alkitabiah yang berkaitan dengan masa lalu di wilayah Israel dan sekitarnya. Kedua, fokusnya harus relevan, sehingga mengabaikan maksud penulis, apa yang dipahami penerima surat. Kitab Suci bukanlah surat yang hanya bisa diselesaikan oleh seorang ahli di bidang akademis. Di satu sisi harus mencari tahu makna teks (bagi penulis dan pembaca), di sisi lain harus menemukan prinsip-prinsip yang bisa diterapkan sekarang dan di sini. Keseimbangan adalah permintaan Firman Tuhan berbicara kepada semua generasi, jadi tidaklah cukup untuk menemukan kembali arti asli dari suatu bagian tanpa menjelaskan pentingnya bagian tersebut untuk hari ini.